Phase Conversion of Ice‐Templated α‐Tricalcium Phosphate Scaffolds into Low‐Temperature Calcium Phosphates with Anisotropic Open Porosity. Issue 5 (28th February 2021) - Seifert, Annika; Groll, Jürgen; Weichhold, Jan; Boehm, Anne V.; Müller, Frank A.; Gbureck, Uwe
Abstract : The current study aims to extend the material platform for anisotropically structured calcium phosphates to low‐temperature phases such as calcium‐deficient hydroxyapatite (CDHA) or the secondary phosphates monetite and brushite. This is achieved by the phase conversion of highly porous α‐tricalcium phosphate (α‐TCP) scaffolds fabricated by ice‐templating into the aforementioned phases by hydrothermal treatment or incubation in phosphoric acid. Prior to these steps, α‐TCP scaffolds are either sintered for 8 h at 1400 °C or remain in their original state. Both nonsintered and sintered α‐TCP specimens are converted into CDHA by hydrothermal treatment, while a transformation into monetite and brushite is achieved by incubation in phosphoric acid. Hydrothermal treatment for 72 h at 175 °C increases the porosity in nonsintered samples from 85% to 88% and from 75% to 88% in the sintered ones. An increase in the specific surface area from (1.102 ± 0.005) to (9.17 ± 0.01) m 2  g −1 and from (0.190 ± 0.004) to (2.809 ± 0.002) m 2  g −1 due to the phase conversion is visible for both the nonsintered and sintered samples. Compressive strength of the nonsintered samples increases significantly from (0.76 ± 0.11) to (5.29 ± 0.94) MPa due to incubation in phosphoric acid. Abstract : Herein, a platform for the phase conversion of aligned porous nonsintered and sintered α‐tricalcium phosphate (α‐TCP) scaffolds into the low‐temperature calcium phosphates such as calcium‐deficient hydroxyapatite (CDHA), brushite, and monetite is presented. This is achieved by hydrothermal treatment or incubation in phosphoric acid solution and has a high clinical potential due to the higher solubility of these phases.